POSHAN’s abstract digest on maternal and child nutrition research - Issue 40 - Avula, Rasmi (International Food Policy Research Institute, 2021)
In this 40th issue of the POSHAN Abstract Digest, we bring to you a collection of articles on the burden of malnutrition in India, its distribution patterns and determinants. You will find several articles focused on nutrition-specific and nutrition-sensitive solutions aimed at improving nutritional outcomes and determinants. This issue also features two articles on data for nutrition, one pertaining to data availability for nutrition financing in India and another describing the current situation of reliable biomarker data availability on micronutrient deficiencies at the global level. We have also included a small section on COVID-19 focused peer-reviewed articles.